A case of neck gas gangrene preceded by mycosis - KAWABATA, Yuko; MARUYA, Shin-ichiro; MAKINAE, Kimitoshi; MATSUBARA, Atsushi; FUJITA, Shigetoshi; SHINKAWA, Hideichi (OTOLOGIA FUKUOKA, 1999)
We experienced a case of neck gas gangrene preceded by mycosis. The patient complained of a sore throat, high fever, and swelling of the neck and pharynx, while a neck abscess with gas was apparent in the parapharyngeal space on a CT scan. After drainage and debridement, the patient's local and general conditions both improved. Anaerobic Streptococcus was identified by a bacterial exam and obsolete candida by a pathological exam. After surgery, the patient was treated by both antibiotics and local irrigation with fluconanzole. We thus concluded that the neck mycosis most likely preceded the formation of the abscess.